Strategies to improve nurses' stress response during the COVID-19 pandemic. Issue 1 (January 2022) - Meehan, Carolyn D.; Schlamb, Cheryl D.; Nair, Julie McCulloh
Abstract : Abstract: Pandemic-related stress factors have been profoundly impacting the wellness of nurses, resulting in job burnout, moral distress, and some nurses deciding to leave the profession. This article examines strategies to identify stressors and develop self-care and coping skills. Abstract : This article examines strategies to identify stressors and develop self-care and coping skills.